Development of Road Traffic Assignment and Assessment Sub-Model Applied in the Traffic Study ... - Topolnik, Dražen; Kljajić, Slobodan; Hozjan, Dubravka (Promet - Traffic&Transportation, 2012)
The described sub-model is just one small segment of theTraffic Study of the City of Zagreb, in the development of whichnumerous foreign and national experts and institutions tookpart. After comprehensive collection and processing of inputdata, the traffic experts, using the software package 'MVATRIPS' for the analysis and search for optimal solutions to theproblem of traffic system, provided the models of public urbantransit for the future.This paper describes the analysis and assessment of sub-models in road traffic assignment for the morning peak, afternoonpeak and average off-peak hours. The principles of assignmentprocedure have been described as well as the convergencetests. The following has been specified: the users categories,the public transit pre-load, and the passenger car unit(PC U). The key guideline in selecting the route is a generalisedformulation of costs presented in the paper. The procedures ofcalibration and the assessment of the finite model have alsobeen defined according to the screenline flows, link flows, andtravelling times. In the end, the summary is given of the basiccharacteristics of the finite travelling matrices.